Modernization in Medical Practices in Rural Nepal: An Ethnographic Study of Hyolmos - Dhakal, Ram Hari (Molung Educational Frontier, 2021)
This article attempts to investigate the modern medical practices and the major factors triggering the changes in views, attitudes, and practices among the Hyolmos, an indigenous people residing in high hill region, Helambu, the northeast of Sindhupalchok, central Nepal. This ethnographic study with the key informants’ interview, participant observation and household census was employed during a year-long fieldwork. The collected data were thematically analyzed and interpreted. The finding shows that the major triggering factors bringing such changes are education, communication, and transportation that increased awareness among the people for choosing alternative opportunities. Tourism and foreign employment raised the economic level that created better financial options for treatment. Conservation of forest was limited to the performance of herbalists and Amchis. To some extent, inter-caste marriage practice and the urbanization process also increased awareness about the use of western medicine.